PENINGKATAN HASIL BELAJAR MEMBACA TEKS TULIS FUNGSIONAL PENDEK BERBENTUK “GREETING CARD” MELALUI MODEL PEMBELAJARAN TGT DI SMP NEGERI 2 KARANGAN - Windu Indarto (Education Journal : Journal Educational Research and Development, 2018)
Teaching and learning English used “teacher center oriented” method hasn’t encourage students’ motivation to gain the determined achievement yet. The fact shows that the second semester students of class VIII D in the year of 2011/2012SMP Negeri 2 Karangan have found difficulties in learning English especially for basic competence 11.2, “ reading functional text about greeting card”. When conducting assessment on reading comprehension, the average students achievement is 68,92 from 24 students. The classical mastery learning rate is 54,17 %. It is still under the Englishlearning minimum criteria (KKM) of the eight grade, namely 70. Therefore, the research is held to overcome the problem through the implementation of Team Game Tournament (TGT) learning method. The learning design is aimed to create “students center” learning activities in order to be able to provide active, creative, joyful and meaningful learning. The classroon action research is held in two cycles. Each consists of 4 steps that are planning, acting, observing and reflecting. In addition there are 2 meeting in each cycle.So there are two data got, from cycle 1 and cycle 2. In conclusion, TGT learning model can enhance the students’ average achievement from 71,25 in cycle 1 into 79,33 in cycle 2.The improvement can also be seen in percentage ofclassical mastery learning, 54,17 in pra cycle, 70,83% in cycle 1 and it becomes 87,50% in cycle 2.